ENHANCING THE STUDENTS SPEAKING ABILITY BY STORY TELLING FOR THE STUDENTS OF SD BINTANG PERTIWI - Wulandari, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study is an experiment with pretest-posttest design through story telling method in learning English towards elementary school students. The subject of this research is the fifth grades students of SDN 106830. This study aims to find out what kinds of stories are suitable for elementary school students and how to implement and what obstacles and solutions need to be taken. This study is in the form of classroom action research with the results of classroom observations as a result during the action, interviews with teachers and students are also conducted to obtain accurate data to complete the data from classroom observations. The results of this study found that the story telling class students achieved better grade, students stated that with the storytelling method, they felt motivated to learn English, happy with class activities, the conducive of classroom atmosphere, and a fun learning process. Based on the problems that have been identified and formulated, the purpose of this study is to answer the questions contained in the problem formulation, namely to find out the story model that is suitable for elementary students, knowing how to implement a story-based learning model for elementary students and to identify problems and find the right solution for improvement.